2020
DOI: 10.1080/21683565.2020.1819513
|View full text |Cite
|
Sign up to set email alerts
|

Farmer experiences of Tiyeni’s ‘deep-bed farming’ conservation agriculture system in Malawi

Abstract: The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRaP URL' above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The average family size of the households’ ranges between five and seven members, and a large family size in the study area is considered an asset. The majority of family members spent their time in the field due to the labor-intensive nature of agricultural activities and the existence of a large number of family members in a household ( Mvula and Dixon, 2021 ). The average farming experience of the smallholder farmers in the area is about 25 years.…”
Section: Resultsmentioning
confidence: 99%
“…The average family size of the households’ ranges between five and seven members, and a large family size in the study area is considered an asset. The majority of family members spent their time in the field due to the labor-intensive nature of agricultural activities and the existence of a large number of family members in a household ( Mvula and Dixon, 2021 ). The average farming experience of the smallholder farmers in the area is about 25 years.…”
Section: Resultsmentioning
confidence: 99%
“…Farm side. At the producer level, most of the research covered effects on land resources & soil health and precision agriculture (Figure 4b) with various sub-topics, including, for example, smart technologies (e.g., O'Shaughnessy et al, 2021), conservation agriculture (e.g., Mvula and Dixon, 2021), and crop rotation and diversification (e.g., Kasu et al, 2019).…”
Section: Ways To Move Forward Towards Sustainable Food Systemsmentioning
confidence: 99%
“…In many cases, producers' decision to adopt sustainable farming practices is motivated by saving money, not having enough money, and maximizing profits, reflecting income & price as the most influential and commonly discussed drivers across geographies and socioeconomic attributes (Figure 2b, Figure 3). For example, farmers might adopt a new sustainable agricultural practice because it saves money due to cheaper production costs and increases revenue due to higher yields, like in the case of Malawian farmers adopting 'deepbed farming', a practice of conservation agriculture (Mvula and Dixon, 2021). Meanwhile, they might not adopt some practices because of the high cost (e.g., the case of farmers in Eastern India who did not adopt farm inputs, machinery, and irrigation (Urfels et al, 2021)).…”
Section: Ways To Move Forward Towards Sustainable Food Systemsmentioning
confidence: 99%
“…However, studies have shown that the long‐term benefits of CA can outweigh these challenges, leading to increased productivity and profitability for farmers (Erenstein et al., 2012; Thierfelder & Mhlanga, 2022). The growing challenges of climate change and limited access to agricultural inputs have highlighted the need for even more innovative and effective techniques to be explored and implemented in SSA, and the deep bed farming (DBF) system promoted by Tiyeni in Malawi, is one such example (Mvula & Dixon, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…All crop residues after harvest are returned to the deep bed as mulches. Although evidence suggests that the DBF system makes a significant contribution to soil and water conservation through reduced runoff and soil erosion (Mvula, 2021), and enhanced maize yields are also reported in many DBF farmers' fields (Mvula & Dixon, 2021), the impacts of legume‐based intercropping systems under the DBF are not well understood. This study aimed to evaluate the effects of incorporating legume‐based intercropping systems involving pigeon pea ( Cajanus cajan ) and cowpea ( Vigna unguiculata ) into the DBF system on soil nutrients and grain yield.…”
Section: Introductionmentioning
confidence: 99%